Bookselling at Northwest Russia in the XIX - early XX centuries (on materials of Saint-Petersburg Province) - S. V. Stepanov (Библиосфера)
The article traces the geographical distribution and bookselling establishments in Saint-Petersburg Province (now Leningrad region) based on unpublished sources. The research identifies factors of St. Petersburg cultural and economic effect on the surrounding areas culture, summer residents’ contribution to the provincial districts development. In the study the following methods are used: content analysis, a technique of analogy, a bibliographic alapproach; main cities - bookselling centres in the region are appointed: Kronshtadt, Narva, Gatchina, Tsarskoe Selo.